DIVERSIFIKASI OLAHAN PEPAYA CALIFORNIA INFERIOR DAN PENGEMASAN PRODUK UNTUK MENINGKATKAN DAYA SAING POTENSI PANGAN - Agus Setiyoko (Universitas Negeri Medan, 2022)
Community service program aimed to increase knowledge and skills regarding the diversification process of “inferior California papaya”, packaging and labeling technology for food products, increasing knowledge about integrated marketing based on information and technology online media in supporting marketing and procurement of production equipments that meets the principles of good processed food production. The community service methods used are: (1) Counseling regarding the diversification of “inferior California papaya”, (2) types and functions of packaging, labels and packaging methods, (3)Training on various papaya preparations including: shredded, chips, lunkhead, fruit juice and papaya sweets, (4) Practise to use a cup sealler machine for packaging, (5) Handover of production equipments. The results of the evaluation of this community service activity are : (1)the knowledge of members regarding the diversification of inferior California papaya processing increased from 8% to 100%, processing skills increased from 17% to 96%, (2) Understanding and ability to make food labels and packaging that meet standards increased from 10% to 92%, (3)Knowledge about the use of production equipment in accordance with the principles of good processed food production methods increased from 8% to 98%, (4) The ability to market their products through online marketing media increased from 10% to 88% and has production equipment that meets standards. Community service program can increase the entrepreneurial spirit of members (PKK Sendi Lestari) and create new business opportunities for the community.Keywords: Diversification, Inferior california papaya, Community service, Packaging.